Employment policy and manpower planning - university of economic science (Berlin university of economic science, 1986)
In practical terms, this book examine the manpower policy and the development therein, it further review the socio-economic objectives of manpower planning resulting from the fact that the power of labour is designed to combine high economic efficiency and human development.
asm; 06/03/19
Loans
Keywords: Unemployment; Berlin